Analysis of the Influence of Human Resource Planning and Development on the Productivity of MSMEs in Bulak District, Surabaya Post the Covid-19 Pandemic - Rina Maretasari; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Digital Bisnis: Jurnal Publikasi Ilmu Manajemen dan E-Commerce, 2023)
In the era of the industrial revolution 4.0, human resources are required to be more sophisticated and advanced in all fields. Internet and technology continue to be put forward in facing every effort and activity against globalization. The following research aims to determine and analyze the influence of planning and human resource development on the productivity of MSMEs in Bulak District, Surabaya after the Covid-19 Pandemic. The following research uses a quantitative approach and the analysis method uses multiple linear regression. The data collection technique in this study used a questionnaire with a sample of 90 respondents. The results of the following study show that planning has a significant effect on productivity because the significance value is 0.000 <0.05. Human resource development has a significant effect on productivity because the significance value is 0.000 <0.05. Planning and development of human resources simultaneously have a significant effect on productivity because the significance value is 0.000 <0.05. Planning and human resource development affect the productivity variable by 63.1% and the remaining 36.9% is explained by other variables outside the model.